Neurodegenerative Disease Treatment Drug PBT2 Breaks Intrinsic Polymyxin Resistance in Gram-Positive Bacteria - David M. P. De Oliveira; Bernhard Keller; Andrew J. Hayes; Cheryl-Lynn Y. Ong; Nichaela Harbison-Price; Ibrahim M. El-Deeb; Gen Li; Nadia Keller; Lisa Bohlmann; Stephan Brouwer; Andrew G. Turner; Amanda J. Cork; et al. (Antibiotics, 2022)
Gram-positive bacteria do not produce lipopolysaccharide as a cell wall component. As such, the polymyxin class of antibiotics, which exert bactericidal activity against Gram-negative pathogens, are ineffective against Gram-positive bacteria. The safe-for-human-use hydroxyquinoline analog ionophore PBT2 has been previously shown to break polymyxin resistance in Gram-negative bacteria, independent of the lipopolysaccharide modification pathways that confer polymyxin resistance. Here, in combination with zinc, PBT2 was shown to break intrinsic polymyxin resistance in Streptococcus pyogenes (Group A Streptococcus; GAS), Staphylococcus aureus (including methicillin-resistant S. aureus), and vancomycin-resistant Enterococcus faecium. Using the globally disseminated M1T1 GAS strain 5448 as a proof of principle model, colistin in the presence of PBT2 + zinc was shown to be bactericidal in activity. Any resistance that did arise imposed a substantial fitness cost. PBT2 + zinc dysregulated GAS metal ion homeostasis, notably decreasing the cellular manganese content. Using a murine model of wound infection, PBT2 in combination with zinc and colistin proved an efficacious treatment against streptococcal skin infection. These findings provide a foundation from which to investigate the utility of PBT2 and next-generation polymyxin antibiotics for the treatment of Gram-positive bacterial infections.